2001
DOI: 10.3758/bf03195754
|View full text |Cite
|
Sign up to set email alerts
|

The effects of attention on perceptual implicit memory

Abstract: Reports on the effects of dividing attention at study on subsequent perceptual priming suggest that perceptual priming is generally unaffected by attentional manipulations as long as word identity is processed. We tested this hypothesis in three experiments by using the implicit word fragment completion and word stem completion tasks. Division of attention was instantiated with the Stroop task in order to ensure the processing of word identity even when the participant's attention was directed to a stimulus at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 61 publications
6
46
1
Order By: Relevance
“…Indeed, priming is often unaffected by divided attention despite marked reductions in explicit memory (e.g., Mulligan 1998). Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001). These relationships concern implicit memory for perceptual stimulus attributes (perceptual priming), whereas conceptual priming is reduced by divided attention to a similar extent as explicit memory (Mulligan 1998;Light et al 2000).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, priming is often unaffected by divided attention despite marked reductions in explicit memory (e.g., Mulligan 1998). Other studies have indicated that divided attention reduces priming to a far lesser extent than explicit memory (e.g., Rajaram et al 2001). These relationships concern implicit memory for perceptual stimulus attributes (perceptual priming), whereas conceptual priming is reduced by divided attention to a similar extent as explicit memory (Mulligan 1998;Light et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…We utilized kaleidoscope stimuli such that verbal encoding and retrieval strategies that typically foster response confidence and retrieval awareness were ineffective. To potentially implicate explicit memory, attentional resources during encoding were manipulated, based on prior findings that reduced attention leads to reduced explicit memory, including both recollection, wherein pertinent details from initial stimulus presentation are retrieved, and familiarity, wherein a feeling of recognition occurs without specific episodic retrieval (Mulligan 1998;Rajaram et al 2001;Yonelinas 2001;Curran 2004). Although it might be argued that we used atypical recognition testing circumstances, the properties of our memory tests were similar to those of recognition tests often given to nonhuman animals; stimuli were nearly meaningless and not likely to be remembered using verbal strategies.…”
mentioning
confidence: 99%
“…RTs have been used to measure the levels of interference caused by competing representations or processes in a number of paradigms-among others, negative priming (Tipper, 1985), repetition priming (Rajaram, Srinivas, & Travers, 2001), and the stop signal RT task (Logan & Cowan, 1984). Blaxton and Neely (1983) showed that RTs to generate the target exemplar were faster if the participant had first read other exemplars from the same category rather than exemplars from a different category.…”
Section: Item-by-item Rifmentioning
confidence: 99%
“…Other studies have reported substantial effects of attentional manipulations on perceptual priming (e.g., Crabb & Dark, 1999Hawley & Johnston, 1991;Rajaram, Srinivas & Travers, 2001;Stone, Ladd, Vaidya, & Gabrieli, 1998). Mulligan (2003a;see also Mulligan, 2002;Mulligan & Hornstein, 2000) identified some of the factors determining whether attentional manipulations affect perceptual priming.…”
mentioning
confidence: 99%